Comparison of testing for failure of passive transfer in calf serum using four different testing methods. (March 2022) - Denholm, K.; Haggerty, A.; Mason, C.; Ellis, K.
Abstract: Failure of passive transfer (FPT) in calves is defined as failure to absorb colostral antibodies sufficient to achieve a serum immunoglobulin G (IgG) concentration of > 10 g/L within the first week of life. The aim of this study was to compare four different tests to diagnose FPT in a convenience sample of 1–7 day old dairy calves in Scotland. Published cutpoints for Brix and total protein (TP) refractometry and zinc sulphate turbidity (ZST) were compared with the reference test radial immunodiffusion (RID) for suitability to detect FPT. In addition, the current commercial RID reference test offered in Scotland was validated. FPT prevalence was estimated to be 14.17% (95% confidence intervals, 10.58–17.75) based on RID test results. There was moderate agreement between the reference (RID) and indirect tests (kappa=0.28 for Brix; 0.34 for TP; 0.24 for ZST). Brix and TP refractometry underestimated IgG concentration, resulting in an overestimation of FPT prevalence (40.54% and 29.46%, respectively). Similarly, ZST overestimated the prevalence of FPT (46.29%), but the variability was more consistent across all IgG concentrations. The performance of all three indirect methods was improved by lowering test cutpoints (to 5 g/dL for TP; 8.2% for Brix; 15 units for ZST) which improved test specificity and accuracy of these screening tests. Highlights: Direct measurement of immunoglobulin G (IgG) in serum is costly and time consuming. Failure of passive transfer (FPT) in calves is often estimated by indirect measures. Zinc sulphate turbidity, Total Protein and Brix estimate serum IgG to detect FPT. Cutpoints defined in previous literature need to be modified for UK usage. Cutpoints for indirect measures need to be lowered to improve test accuracy.